Assessing the sociology of sport: On media and power. (June 2015) - Rowe, David
On the 50th anniversary of the ISSA and IRSS, a key international figure in the study of media and sport within the sociology of sport, David Rowe, reflects on the field as a whole and the role for studying media and power within it. Rowe considers how some development in the sociology of sport within the larger discipline of sociology may be seen as 'gestural and instrumental'. In considering the challenges of the field, Rowe notes how the media serves to situate and amplify sport's inherent powers of 'liveness', whether sport is manifest in mega-events or in 'extraordinary ordinariness'. The closing section of the essay focuses on questions of media and power, foremost those concerning spectacle and commodification and their intersection with politics and the transactions of nationalized identities with those of race, ethnicity and gender in a globalized media sports cultural complex.